Women in fintech: uncovering the snags through systematic assessment and bibliometric investigation - Minyu, Zheng; Mohd Nor, Normaziah; Mohammad Saif, Abu Naser; Anwarul Islam, K. M.; Bari, Md. Fakhrudoza (Inderscience Publishers, 2022)
Financial technology (Fintech) has transfigured business excellence making the globe smaller. In contrast, as women’s representation in Fintech has been on a low trajectory, the present systematic assessment with bibliometric investigation aims to uncover the extensive clusters of snags for women in Fintech (WIFT). From a total of 194 documents published between 2016 and 2022 and archived in four mainstream research databases, 14 relevant publications were traced using the PRISMA flowchart. Bibliometric information was compiled from each of the 14 publications. Significant terms were revealed by crafting word co-occurrence network maps with VOSviewer 1.6.18. Different allied snags were reported by thoroughly reviewing the identified papers. The cross-mapping procedure documented extensive clusters of themes, such as social inequality, Fintech literacy, and psychological construct. The findings indicate that social inequality, Fintech literacy, and psychological construct remain major snags for WIFT.